Silages prepared from different maize hybrids effect in-vitro rumen fermentation parameters and growth performance in crossbred calves - SINGH, SHWETA; TYAGI, AMRISH KUMAR; KALE, VISHNU (The Indian Journal of Animal Sciences, 2014)
The experiment was conducted to evaluate the effects of silages prepared from different maize varieties/hybrids on fermentation characteristics, microbiological characteristics, and growth performance in growing crossbred calves. Female crossbred calves (18) of 4–5.5 months of age were selected and distributed randomly into 3 treatment groups of 6 animals each, based on their body weight. All the calves of 3 groups were offered silages prepared from different varieties/hybrids (control - Vijay composite, T1 - DKC 9108 and T2 - 900M Gold) and concentrate in 70: 30 ratio in 105 days of experimental period. Metabolism trial was conducted to assess feed intake, nutrients utilization and N balance. In vitro gas/methane production and digestibility trials were carried out for 24 h and 48 h respectively. In vitro methane production was higher in T1 than control and T2. The total DMI (kg/day) as well as body weight change in crossbred calves was similar in 3 groups throughout the experimental period. TDNI (kg/day) and NDF digestibility was significantly higher in T1 than control and T2 groups. CP digestibility was higher in control and T1 than T2. The results showed that DMI and growth performance of calves were similar in 3 groups notwithstanding the different chemical composition as well as different microbial characteristics of silages prepared from different maize varieties/hybrids. However methane production differed significantly among the groups which can be an area of interest for further mitigation studies.